Effect of ethyl oleate on drying characteristics of mulberries - Doymaz, I; Pala, M (WILEY-V C H VERLAG GMBH, 2003)
In this study, air-drying experiments in thin layers of mulberry grown in Istanbul, Turkey, were conducted. The effect of ethyl oleate solution on drying time of mulberry samples was investigated in a pilot air-dryer. When ethyl oleate was used as pretreatment solution, the drying time of samples was decreased. Drying curves were obtained using the Page model. The effective diffusivity varied from 2.326 x 10(-10) to 1.809 x 10(-9) m(2)/s the temperature range. The temperature dependence of the diffusivity coefficient was described by the Arrhenius type relationship. The activation energy for moisture diffusion was found to be 50.87 kJ/mol for treated samples and 51.85 kJ/mol for untreated samples.
Keywords: activation energy; drying characteristics; mulberry; pretreatment solution; DIPPING TREATMENT; SULTANA GRAPES; AIR; PRETREATMENTS; DEHYDRATION; ISOTHERMS; APRICOTS; KINETICS; RAISINS; SLICES; Food Science & Technology